Defining a Taxonomy of Intracranial Hypertension: Is ICP More Than Just a Number? - Kofke, W Andrew (J Neurosurg Anesthesiol, 2020)
Intracranial pressure (ICP) monitoring and control is a cornerstone of neuroanesthesia and neurocritical care. However, because elevated ICP can be due to multiple pathophysiological processes, its interpretation is not straightforward. We propose a formal taxonomy of intracranial hypertension, which defines ICP elevations into three major pathophysiological subsets: increased cerebral blood volume, masses and edema, and hydrocephalus. 1. Increased cerebral blood volume increases ICP and arises secondary to arterial or venous hypervolemia. Arterial hypervolemia is produced by autoregulated or dysregulated vasodilation, both of which are importantly and disparately affected by systemic blood pressure. Dysregulated vasodilation tends to be worsened by arterial hypertension. In contrast, autoregulated vasodilation contributes to intracranial hypertension during decreases in cerebral perfusion pressure that occur within the normal range of cerebral autoregulation. Venous hypervolemia is produced by Starling resistor outflow obstruction, venous occlusion, and very high extracranial venous pressure. Starling resistor outflow obstruction tends to arise when cerebrospinal fluid pressure causes venous compression to thus increase tissue pressure and worsen tissue edema (and ICP elevation), producing a positive feedback ICP cycle. 2. Masses and edema are conditions that increase brain tissue volume and ICP, causing both vascular compression and decrease in cerebral perfusion pressure leading to oligemia. Brain edema is either vasogenic or cytotoxic, each with disparate causes and often linked to cerebral blood flow or blood volume abnormalities. Masses may arise from hematoma or neoplasia. 3. Hydrocephalus can also increase ICP, and is either communicating or non-communicating. Further research is warranted to ascertain whether ICP therapy should be tailored to these physiologic subsets of intracranial hypertension.